The role of miRNAs and endogenous siRNAs in maternal-to-zygotic reprogramming and the establishment of pluripotency - Svoboda, Petr; Flemr, Matyas (EMBO reports, 2010)
RNA silencing is a complex of mechanisms that regulate gene expression through small RNA molecules. The microRNA (miRNA) pathway is the most common of these in mammals. Genome-encoded miRNAs suppress translation in a sequence-specific manner and facilitate shifts in gene expression during developmental transitions. Here, we discuss the role of miRNAs in oocyte-to-zygote transition and in the control of pluripotency. Existing data suggest a common principle involving miRNAs in defining pluripotent and differentiated cells. RNA silencing pathways also rapidly evolve, resulting in many unique features of RNA silencing in different taxonomic groups. This is exemplified in the mouse model of oocyte-to-zygote transition, in which the endogenous RNA interference pathway has acquired a novel role in regulating protein-coding genes, while the miRNA pathway has become transiently suppressed.
Keywords: RNA interference; sekvence nukleotidů; MicroRNAs; oocyty; fylogeneze; Pluripotent Stem Cells; mikro RNA; Phylogeny; zygota; molekulární sekvence - údaje; sekvenční seřazení; pluripotentní kmenové buňky; RNA, Small Interfering; Animals; lidé; Humans; malá interferující RNA; zvířata; Molecular Sequence Data; Base Sequence; Zygote; RNA Interference; Sequence Alignment; Oocytes